Sonographic renal length in Malaysian infant population - a hospital based cross section study - Halim Lim, Aidi Aswadi; Abd. Aziz, Azian (2021)
Objective: The neonatal stage is an important period of organ development whereby an insult could result in organ impairment. The kidneys demonstrate similar predisposition. Renal ultrasonography is crucial in examining the kidneys, including the renal length. The lack of local data means Malaysian doctors are dependent on data from other populations, which may not be locally suitable. Therefore, the objective of this paper is to determine the range of normal sonographic renal length amongst infant up to 1 year old in IIUMMC and HTAA Kuantan, Malaysia, to investigate sonographic renal lengths differences between male and female infants and to propose simple mathematical equations to estimate ideal renal length based on infant’s age. Materials & Methods: All children under the age of 1 who had normal ultrasound of the kidneys were included. Five age groups were formed based on examples from previous studies. Data were mined from the Radiology Information Systems of both centres. 463 cases were selected. Important data were obtained – the infant’s age, gender and their sonographic renal lengths for both kidneys. Their respective sonographic renal lengths were tabulated according to their age group, following which a group mean and 95% confidence interval were derived. Results: We tabulated the means and 95% confidence intervals for both right and left kidneys separately for each group. No significant difference in the sonographic renal lengths between the genders identified. Two separate linear regression equations were formulated for the right and left kidneys. Conclusion: We formulated a table of normal sonographic renal lengths according to age for infants, useful in day-to-day practice.